The Utilization of Smartphones in The Digital Era as Interactive Learning Tools for Sociology Lessons in High School. - Fathan Syuhada Kurniawan; Sariyatun Sariyatun; Herry Widyastono (AIBPM Publisher, 2022)
The improvement of Technology and Information encourages diverse residing factors to open up for the advantages of the net in coaching and gaining knowledge of activities. Thereby, the academics will not be able to get admission to the net as a medium to supply the cloth to guide students' capacity to adsorb and recognize the lessons. This research makes use of a descriptive qualitative studies method. A social research scholar studied this situation in elegance XI High School with 149 college students. Data series for these studies is survey that additionally interviews. Data evaluation is achieved on four levels: data analysis, data reduction, data presentation, and conclusions. The conclusions of this research display that there had been high-quality possibilities for using smartphones withinside the virtual technology in gaining knowledge, especially in sociology training in High School. These possibilities are the utility of net-primarily based cellular gaining knowledge. It is understood that the whole college students have additionally frequently used smartphones for social media, games, etc. The end of this study is net media is a high-quality possibility to apply the cellphone withinside the virtual technology as interactive gaining knowledge of device for sociology training in excessive school.Â Keywords: Digital gaining knowledge, Internet media, Mobile, Learning, Sociology Learning, Utilization of Smartphones.